LICENSEE’S PERCEPTION IN THE INTRODUCTION OF THE PEDAGOGIA RESIDENCE PROGRAM IN THEIR TRAINING AT THE FACULTY OF EDUCATION OF CRATEÚS - Ferreira do Nascimento, Eva; Da Silva Lacerda Junior , Orivaldo (Revista Gênero e Interdisciplinaridade, 2022)
The main objective of this work is to analyze the perceptions that the members of the Pedagogical Residency Program have in relation to the program in which they are linked. The work deals with a bibliographical research which emphasizes important points of the professional teaching career, such as the importance of the Pedagogical Residency program in the lives of undergraduates, theory in relation to practice, a brief summary of the history of the formation of initial teachers and the job market for teachers. In order to carry out this monographic work, a qualitative research was carried out through Google forms, in which eleven fellows from the group of undergraduate students of the Chemistry course at the Faculty of Education of Crateús participated, the research had five questions in which all were about obligatory objective questions. As a result, it can be concluded that the program is very important in the lives of future teachers, mainly because it allows teachers to have a broad view of what their chosen profession really is.